Racial tension, public mistrust, and policing: Insights from police leaders in the Rio Grande Valley (RGV)- a research note - Dawkins-Cavazos, Marika (Journal of ethnicity in criminal justice, 2022)
This paper presents preliminary insights from police leaders in the Rio Grande Valley (RGV), a southwestern border region of the United States. Perceptions among minority police leaders with respect to minority-police interactions have received little attention. To better understand the perceptions of minority police leaders, this study focused on whether police leaders in a predominantly Hispanic region of the country perceive that racial tensions influence police-community interactions. Using a purposive sample of 29 police leaders, preliminary results suggest that recent high-profile incidents have had some impact on how officers do their jobs. Implications for public policy and suggestions for future studies are discussed.